(3QSGdI GdCNdGbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI bGd Gdebfj jG ef faSg GdeMH deYQaI GdaVGFd hcjajI GbJfGFgG s
(3BNQgG (B:s
(3hEfeG jYhOhfge ef CaYGd GdNjQ hcPdc CUMGH GdSjGSGJ GdQOjFI s
(3Vef eLehY , JQJjHgG (B: 6s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs